2000
DOI: 10.1007/s002230050004
|View full text |Cite
|
Sign up to set email alerts
|

Bone Ultrasonometry and Turnover Markers in Primary Hyperparathyroidism

Abstract: Quantitative ultrasound (QUS) of bone and new markers of bone remodeling have been poorly investigated in mild primary hyperparathyroidism (PHPT). In this study 26 patients (20 females and 6 males) were evaluated. BUA and SOS were measured by QUS at the heel. Markers of bone remodeling assessed were bone alkaline phosphatase (BAP), osteocalcin (OC), procollagen type I N- and C-terminal propeptides (PINP et PICP), and procollagen type I C-terminal telopeptide in blood and urine (ICTP and CTX). Bone mineral dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
4

Year Published

2001
2001
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 24 publications
1
6
0
4
Order By: Relevance
“…Two previous studies have shown similar results in urinary CTX-I with baseline BUA [21,22]. A few earlier studies have shown that urinary CTX-I [18,33,40,41] and S-CTX-I [13,28] were associated with DXA-based aBMD changes.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Two previous studies have shown similar results in urinary CTX-I with baseline BUA [21,22]. A few earlier studies have shown that urinary CTX-I [18,33,40,41] and S-CTX-I [13,28] were associated with DXA-based aBMD changes.…”
Section: Discussionsupporting
confidence: 55%
“…Patients with fractures [23] or individuals with endocrine disorders [22] have been investigated. Compared to this study, the studies listed above included limited number of women (n=from 26 to 110) and only few BTMs analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…QUS of the heel reflects trabecular bone status, bone quality and predicts fracture risk [7,8]. Numerous QUS studies have been carried out in postmenopausal osteoporosis and other endocrine disorders that affect bone metabolism, such as primary hyperparathyroidism and hyperthyroidism, or during pregnancy and lactation when hormonal status changes [9][10][11][12][13]15]. …”
Section: Discussionmentioning
confidence: 99%
“…QUS has been applied in some metabolic and hormonal bone diseases such as osteoporosis, Cushing's syndrome, hyperthyroidism and primary hyperparathyroidism [10][11][12][13]. To our knowledge QUS of the heel has not been studied in acromegaly.…”
Section: Introductionmentioning
confidence: 99%